2021
DOI: 10.3390/ijerph18189743
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management of COVID-19 in the Residential Educational Setting: Lessons Learned and Implications for Moving Forward

Abstract: With limited COVID-19-guidelines for institutions of higher education (IHEs), colleges and universities began the 2020–2021 academic year with varying approaches. We present a comprehensive COVID-19 prevention and mitigation approach at a residential university during the 2020–2021 academic year, along with campus SARS-CoV-2 transmission during this time. Risk management of COVID-19 was facilitated through (1) a layered approach of primary, secondary, and tertiary prevention measures; (2) a robust committee st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…This would then reserve resources for increased sampling during periods of high transmission when the reduction in infections per test is high. A similar strategy appeared to provide favorable results at Furman University (13). This conclusion is similar to Paltiel et al (39) effective, and to Hambridge, Kahn, and Onnela (34), who found that increasing the frequency of surveillance testing has smaller effects on the infection rate when R 0 is low than when it is high.…”
Section: Sampling Strategy For Surveillance Testingsupporting
confidence: 77%
See 3 more Smart Citations
“…This would then reserve resources for increased sampling during periods of high transmission when the reduction in infections per test is high. A similar strategy appeared to provide favorable results at Furman University (13). This conclusion is similar to Paltiel et al (39) effective, and to Hambridge, Kahn, and Onnela (34), who found that increasing the frequency of surveillance testing has smaller effects on the infection rate when R 0 is low than when it is high.…”
Section: Sampling Strategy For Surveillance Testingsupporting
confidence: 77%
“…The copyright holder for this preprint this version posted January 13, 2023. ; https://doi.org/10.1101/2023.01. 13.23284515 doi: medRxiv preprint 4 Further, university-owned residences are differentiated from other residential facilities (e.g., hospitals, long-term care facilities, prisons) through the multiscale population mixing that is inherent to campus communities. On a local level, university students regularly mix with surrounding communities through student employment, peers in off-campus housing, interactions with friends and family outside of the university, and participation in community events.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As of June 2021, there have been 173 million COVID-19 cases worldwide, with new cases rapidly increasing at an alarming rate and showing no signs of abating [1]. If COVID-19 infection is not detected early enough, it can induce a flu-like sickness that can proceed to acute respiratory distress syndrome (ARDS), which can be deadly [2][3][4][5][6][7][8]. Due to limited resources and the amount of data accessible to the scientific community, early diagnosis of COVID-19 remains a tough challenge despite recent worldwide research efforts in healthcare [9].…”
Section: Introductionmentioning
confidence: 99%